Global pathways to water sustainability - McNabb, David E. (Cham, Switzerland : Palgrave Macmillan, 2019)
This book investigates the current and future state of freshwater and the global drive to achieve the UN sustainability goal. It first explores the major barriers to achieving the goal and then examines some of the programs water managers are adopting to overcome those barriers. These programs include finding new ways to supplement existing water supplies, and greater acceptance of alternative supplies, such as recycled waste water and desalination; green infrastructures, and rain and storm water harvesting. It concludes with two chapters on water management tools, including asset management and strategic planning, which are of particular interest to small water and wastewater utilities.
Includes bibliographical references and index.
Keywords: Water-supply -- Management; Water resources development; Freshwater ecology; Sustainable development